2020
DOI: 10.1017/ice.2020.785
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated With Inappropriate Antibiotic Use in Hospitalized Patients

Abstract: Background: Inappropriate antibiotic prescription leads to increased Clostridiodes difficile infections, adverse effects including organ toxicity, and generation of antibiotic-resistant bacteria. Despite efforts to improve antibiotic use in acute-care settings, unnecessary and inappropriate prescription still occur in 30%–50% of patients. Objectives: We assessed factors associated with inappropriate antibiotic prescription at 2 time points: (1) initial, empiric therapy and (2) 3–5 days after therapy initiation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
1
1
Order By: Relevance
“… 24 On the other hand, patients who were taking vancomycin had nearly three times at increased risk of inappropriate AMT use than patients not taking it. This is different from Pakistan, 28 Switzerland, 32 and Maryland 49 studies, where cephalosporin use, penicillin with β-lactamase inhibitors and cephalosporin use, and cefepime or piperacillin-tazobactam use were factors associated with inappropriate use of antibiotics, respectively. This inconsistency might be due to the possibility of variation in the availability, cost, and utilization of antibiotics across the countries.…”
Section: Discussioncontrasting
confidence: 67%
“… 24 On the other hand, patients who were taking vancomycin had nearly three times at increased risk of inappropriate AMT use than patients not taking it. This is different from Pakistan, 28 Switzerland, 32 and Maryland 49 studies, where cephalosporin use, penicillin with β-lactamase inhibitors and cephalosporin use, and cefepime or piperacillin-tazobactam use were factors associated with inappropriate use of antibiotics, respectively. This inconsistency might be due to the possibility of variation in the availability, cost, and utilization of antibiotics across the countries.…”
Section: Discussioncontrasting
confidence: 67%
“…In a multicenter study, older age, prescription in summer were detected as risk factors for initial inappropriate antibiotic use, while end-stage renal disease was found to be a protective factor from inappropriate use. In the same study patients receiving cefepime or piperacillin-tazobactam were reported to be at greater risk of receiving inappropriate antibiotics on days 3–5 due to the failure to de-escalate [ 44 ]. Elderly people are often hospitalized as there is a higher risk of infection and infection-related adverse outcomes, multiple comorbidities and polypharmacotherapy.…”
Section: Discussionmentioning
confidence: 99%